1992
DOI: 10.1007/bf01447447
|View full text |Cite
|
Sign up to set email alerts
|

Cathode erosion on copper electrodes in steam, hydrogen, and oxygen plasmas

Abstract: Experimental data are presented for cathode erosion rates on copper cathodes .for magnetically rotated arcs in steam, and mixtures of steam, hydrogen, and oxygen with argon. Measurements were also made of the arc voltage and velocity. The erosion rates.for steam and oxygen plasmas were significantly lower than those.lbr argon and hydrogen. Pure steam and 10% oxygen in argon gave erosion rates o.f 2.3 and 6.1 l.tg/ C respectively while pure argon and 70% hydrogen in argon gave rates of 14.8 and 13.0 ~g/ C respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Results obtained up to 1994 and reported by Szente et al (1987aSzente et al ( , b, 1989Szente et al ( , 1990aSzente et al ( , b, 1991Szente et al ( , 1992, Munz and Habelrich (1992), Teste (1994), Gleizes (1995), Meunier et al (1992), and Meunier and Desaulniers-Soucy (1994) were obtained at atmospheric pressure for different plasma gases (Ar, He, CO, N 2 , O 2 , Cl 2 , H 2 S, CH 4 , Air) gas flow rates and magnetic flux densities from 0 to 0.15 T, with either cylindrical electrodes (Szente et al 1992) or rotating disk electrodes (Teste 1994). The most important conclusions are the following:…”
Section: Cathode Materials and Erosionmentioning
confidence: 73%
See 1 more Smart Citation
“…Results obtained up to 1994 and reported by Szente et al (1987aSzente et al ( , b, 1989Szente et al ( , 1990aSzente et al ( , b, 1991Szente et al ( , 1992, Munz and Habelrich (1992), Teste (1994), Gleizes (1995), Meunier et al (1992), and Meunier and Desaulniers-Soucy (1994) were obtained at atmospheric pressure for different plasma gases (Ar, He, CO, N 2 , O 2 , Cl 2 , H 2 S, CH 4 , Air) gas flow rates and magnetic flux densities from 0 to 0.15 T, with either cylindrical electrodes (Szente et al 1992) or rotating disk electrodes (Teste 1994). The most important conclusions are the following:…”
Section: Cathode Materials and Erosionmentioning
confidence: 73%
“…Since rapid movement of the arc roots will reduce electrode erosion, many theoretical studies were devoted to the movement of the arc in a magnetic field (Guile and Naylor 1968;Guile and Hitchcock 1975;Roman and Meyers 1966). These studies express the fact that the Lorentz force acting on the arc due to an external magnetic induction, B, is balanced by a force equivalent to drag forces (aerodynamic drag and "surface drag") which retards the motion (Szente 1987b;Munz and Habelrich 1992):…”
Section: Cathode Materials and Erosionmentioning
confidence: 99%
“…In operation with contaminated nitrogen, the effect of the composite is still appreciable, causing more than a doubling in velocity. Finally, previous experiments with hydrogen gas mixtures showed that hydrogen was rather ineffective in reducing surface drag (Munz and Habelrih 1992). The increase in velocity as hydrogen was added may have been entirely due to the reduction in the density of the gas through which the arc passed and thus a reduction in aerodynamic drag.…”
Section: Arc Velocitiesmentioning
confidence: 87%
“…The resulting relation can be expressed as The combination of Eqs. (3) and (4) gives vocy -°225 (5) which predicts that the arc velocity should decrease as the TiCI4 concentration increases. If chemical reactions are included in the analysis, the coefficient in Eq.…”
Section: Experiments With Tici4-argon Plasma Gasmentioning
confidence: 96%